Natural source zone depletion (NSZD) insights from over 15 years of research and measurements: A multi-site study. (15th October 2022) - Kulkarni, Poonam R.; Walker, Kenneth L.; Newell, Charles J.; Askarani, Kayvan Karimi; Li, Yue; McHugh, Thomas E.
Highlights: Site-average NSZD rates compiled from 40 LNAPL sites with a median of 9, 450 L/ha/yr. No significant differences in rates between sites with different fuel types. Measurement method comparisons resulted in a median ratio of 2.1 (max/min). NSZD rates typically higher in summer and fall compared to winter and spring at some sites. Median Q10 value of 2.2, indicates an increase of 10°C could potentially double NSZD rates. Abstract: Site-average Natural Source Zone Depletion (NSZD) rates measured from 40 petroleum light non-aqueous phase liquid (LNAPL) source zone sites were compiled from researchers, project reports, and scientific papers. At each site, the following data were compiled: i) general site location; ii) LNAPL fuel type; iii) measurement method, number of locations, and number of measurements per location; and iv) calculated site-average NSZD rate in liters per hectare per year (L/ha/yr) per site and the associated measurement method (i.e., Gradient Method, Carbon Traps, Dynamic Closed Chamber (DCC), or Thermal Monitoring). The resulting dataset showed site-average NSZD rates that ranged from 650 to 152, 000 L/ha/yr (70 to 16, 250 gallons per acre per year (gal/acre/yr)), with a median value of 9, 540 L/ha/yr (1, 020 gal/acre/yr). The median site-average NSZD rate by type of fuel spill did not show a statistically significant difference between fuel types. When comparing the different NSZD measurement methods applied to the same sites, the site-average NSZD rates differed by up to 4.8 times (i.e., ratio of faster rate to slower rate), with a median difference of 2.1 times. No clear bias was observed between NSZD rate measurement methods. At four sites with calculations of NSZD rates by season, NSZD rates were typically higher during summer and fall compared to winter and spring. For these sites, Q10 values (a measure of the increase in NSZD rate associated with a 10 °C increase in temperature) ranged from 0.8 to 15.1, with a median of 2.2. The implications of this study suggest that increasing mean annual soil temperature at a site using engineered methods could potentially increase the biodegradation rate (e.g., an increase of 10 °C could double the NSZD rate). Finally, for five sites with site-average NSZD rates for multiple years, average NSZD rates varied by 1.1 to 4.9 times across years. Overall, the evaluation of NSZD rates measured at 40 LNAPL sites suggests that measurable NSZD occurs across a broad range of LNAPL sites. Although NSZD rates vary across sites, fuel type is not the primary factor explaining observed differences in rates. Graphical abstract: Image, graphical abstract